EXPANDING THE ONLINE COMMUNICATION FUNCTIONALITY OF THE HELSI MEDICAL INFORMATION SYSTEM - ПАНАСЮК, О. І.; ПЛЕСКАЧ, В. Л.; МОЛЧАНОВ, Б. С. (Technologies and Engineering, 2023)
Purpose. Based on a comparative analysis of the two popular DBMS MongoDB and Redis, determine the best one for expanding the functionality of the existing applied information system. Create a new service to provide real-time communication via a websocket connection for the HELSI medical information system. When creating a database, take into account the possibility of high load and the need to add data aggregation in subsequent iterations of the functionality. Methodology. The functionality was implemented using the C# 10.0 language, the ASP.NET Core 6.0 framework, and the MongoDB database. Findings. An analytical study and comparison of the MongoDB and Redis DBMSs was carried out in terms of performance, security, type of data storage system and type of internal language. It is proposed to use a combination of the SignalR Core library for the .NET 6 platform together with the MongoDB DBMS to provide management of connections using the Websocket protocol in a highly loaded medical information system during an online chat between a patient and a doctor. A new service has been developed to provide real-time communication through a websocket connection for the medical information system HELSI. Originality. Theoretical and methodological approaches to the comparative assessment of the characteristics of modern NoSQL DBMS and the application of hybrid approaches to the combination of technologies, which are used in the development of application software in the construction of software systems, have been developed. Practical value. Using the C# 10.0 programming language and the .NET 6 platform and the MongoDB database, the functionality of the existing applied medical information system HELSI has been expanded with the possibility of a chat between the doctor and the patient during online appointments. A database has been designed to store information related to this functionality. Accompanying documentation for the development of the interface for the created functionality has been prepared.